Coherence and organisation in lanthanoid complexes: from single ion magnets to spin qubits. Issue 5 (29th February 2016) - Gaita-Ariño, Alejandro; Prima-García, Helena; Cardona-Serra, Salvador; Escalera-Moreno, Luis; Rosaleny, Lorena E.; Baldoví, José J.
Abstract : Molecular magnetism is reaching a degree of development that will allow for the rational design of sophisticated systems. Abstract : Molecular magnetism is reaching a degree of development that will allow for the rational design of sophisticated systems. Among these, here we will focus on those that display single-molecule magnetic behaviour, i.e. classical memories, and on magnetic molecules that can be used as molecular spin qubits, the irreducible components of any quantum technology. Compared with candidates developed from physics, a major advantage of molecular spin qubits stems from the power of chemistry for the tailored and inexpensive synthesis of new systems for their experimental study; in particular, the so-called lanthanoid-based single-ion magnets, which have for a long time been one of the hottest topics in molecular magnetism. They have the potential to be chemically designed, tuning both their single-molecule properties and their crystalline environment. This allows the study of the different quantum processes that cause the loss of quantum information, collectively known as decoherence. The study of quantum decoherence processes in the solid state is necessary to answer some fundamental questions and lay the foundations for next-generation quantum technologies. This perspective article reviews the state of the art research in this field and its currently open problems.